PENGARUH PEMBELAJARAN IPAS MELALUI PENDEKATAN COMPUTATIONAL THINKING BERBASIS SCRATCH TERHADAP KEMAMPUAN BERPIKIR KRITIS DAN KOMUNIKASI SISWA SEKOLAH DASAR - Eka Nugraheni, Dian; Anggoro, Subuh; Dyah Purwandari, Ristiana; Gunawan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Indonesian students' critical thinking skills remain low, reflected in the 2022 PISA results, where Indonesia ranked 69th of 80 countries, with only 0.9% of students reaching level 4–6 higher-order thinking questions in science. A diagnostic test given to 16 fourth-graders at SD Negeri 2 Kesenet, Banjarmangu, Banjarnegara, showed an average score of only 59, far below the mastery criterion, with students struggling to explain reasoning and analyze cause-and-effect relationships on the abstract topic of